Advances of Future IoE Wireless Network Technology - Horng, Gwo-Jiun; Aripriharta, S.T; Tsou, Yao-Tung; Tsai, Chia-Wei (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The aim of this reprint is to report on new scenarios, technologies, and applications related to the concept of the Internet of Everything and discuss challenges and risks. We introduced a wide range of topics related to emerging technologies. This reprint includes research on vendor-managed inventory mechanisms based on the SCADA of the Internet of Things, in-memory computing architecture for a convolutional neural network, face prediction system for missing children in a smart city safety network, anomaly electricity usage behavior in residence using an autoencoder, cloud-edge-smart IoT architecture for speeding up the deployment of neural network models, generative adversarial network and diverse feature extraction methods to enhance the classification accuracy of the tool-wear status, classifying conditions of speckles and wrinkles on the human face using a deep learning approach, repetition with learning approaches in massive machine-type communications, GDPR personal privacy security mechanism for smart home systems, and the development of an autonomous vehicle training and verification system. These articles demonstrate the rapid advances being made in the field of electronics and highlight the potential for these technologies to impact our daily lives.